Construction of pH-sensitive targeted micelle system co-delivery with curcumin and dasatinib and evaluation of anti-liver cancer. (31st December 2022) - Zeng, Xiangle; Zhang, Yawen; Xu, Xue; Chen, Zhuo; Ma, Lanlan; Wang, Yushuai; Guo, Xuliang; Li, Jianchun; Wang, Xiu
Abstract: Nanomedicine delivery systems can achieve precise drug delivery and reduce toxic side effects compared with traditional drug delivery methods, but further development is still needed to eliminate obstacles such as multiple drug co-delivery, uncontrolled drug-release, and drug-resistance. Herein, we designed a dual drug-loaded nanosystem (THCD-NPs) that selectively transports and targets tumor cells for the treatment of liver cancer. In this drug delivery system, hyaluronic acid (HA)-conjugated curcumin (Cur) and d -α-tocopherol acid polyethylene glycolsuccinate (TPGS) were used as selective drug-carrying vehicles to deliver dasatinib (DAS) to cancer cells for combined administration. The mean size of the nanoparticles was approximately 66.14 ± 4.02 nm with good in vitro stability. The nanoparticles were pH sensitive and could accelerate drug release at low pH conditions. In vitro experiments showed that THCD-NPs were significantly cytotoxic to HepG2 cells and could be effectively taken up by these cells. Detailed investigations also demonstrated its pro-apoptotic activity. In vivo NIR fluorescence imaging showed that the nanoparticles could accumulate efficiently at the tumor site. Meanwhile, in vivo experiments showed that THCD-NPs significantly inhibited tumor growth and reduced the toxic side effects of free drugs in a mouse solid tumor model. In short, the nanoparticles we prepared provide a new idea for the treatment of liver cancer.